Agrokoncerny - czyj biznes, czyje problemy - Woźniak, Leszek (Agriconcerns - Whose Business, Whose Problems, 2005)
The paper presents results of research of agriconcern. They are definitely negative. Examples are given from the USA and from Poland - before its accession to the European Union.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 416-422